Human impact on wetland flora of the Warsaw-Berlin proglacial valley - Kopeć, Dominik; Halladin-Dąbrowska, Anna; Chmielecki, Błażej; Kucharski, Leszek (Biodiversity: Research and Conservation, 2008)
Central Poland is a region with low wetland richness. Its most valuable meadows and peatlands are situated in the eastern part of the Warsaw-Berlin proglacial valley, between Łowicz and Dąbie. This largest wetland area of Central Poland covers ca. 20 000 hectares, with a mosaic of meadows, forests, various wetlands, and small areas of arable land. Over the last 50 years, a negative impact of agriculture has been observed in the plant cover at the bottom of the proglacial valley, e.g. extinction of many wetland plant species. The main aim of this research was to determine the impact of agriculture on floristic diversity and natural condition of the wetland. In the 77 studied squares (1 km2each), we recorded ca. 600 species of vascular plants. The squares greatly varied in species composition and number. The long-term human pressure on the proglacial valley flora caused its significant degradation: with the progress of transformation of the area, the participation of anthropophytes and apophytes increases. Additionally, intensive agriculture in the proglacial valley causes extinction of species from wetland habitats.